Effects of feces storage conditions for host-microbiota screenings in C. elegans - Caron, Laury; Alonzo De la Rosa, Claudia Miriam; Diop, Khoudia; Miard, Stéphanie; Taubert, Stefan; Marette, André; Picard, Frédéric (Frontiers in Microbiomes, 2024)
Background and aimsCurrent research on host-gut microbiota interactions is hindered by almost infinite bacterial combinations depending on intrinsic characteristics, environment, and health status, which prevents large-scale screenings in mammals. For these reasons, the bacterivore model organism C. elegans has been developed to test the effects of gut microbiota extracts from mammals. This study tested whether storage conditions of mouse feces and fecal extracts modify normal C. elegans healthspan.MethodsFeces from mice were processed for microbiota extraction after collection or after one or twelve months at -80 °C and compared to microbiota extracted six months before and left at room temperature. Extracts were probed for bacterial composition, viability, and nutritional content and tested in synchronized wild-type (strain N2) worms for food preferences and intake, development, fat accumulation, brood size, and maximal lifespan.ResultsLong-term freezing of feces before microbiota extraction modified composition but did not negatively impact subsequent worm development, fat accumulation, reproduction, and maximal lifespan, whereas using samples extracted and left at room temperature after a long period of time resulted in robust avoidance and was detrimental for normal growth.ConclusionsUsing frozen feces to test for impacts of microbiota in C. elegans appears an appropriate method since it did not affect normal biology and healthspan, which supports protocols with already existing feces stored in biobanks for high-throughput phenotype screenings.